Effektivität der Sklerosierungstherapie in Abhängigkeit vom Alter der Patienten - Kahle, Birgit; Flux, Katharina; Schliephake, D.; Recke, A. (Phlebologie, 2010)
In clinical practice sclerotherapy of intradermal varicose veins seems to be more effective in elderly patients. Patients, methods: After prior duplex-sonographic investigation 48 patients with intradermal varicose veins (diameter 1-2 mm, C1,EP, AS, PR) were included. 24 patients (group 1) received Polidocanol (0.25% Aethoxysklerol®) injection sclerotherapy and 24 patients (group 2) received sodium chloride injections. In all subjects an area of 100 square centimetres of the lower limb was treated. The borders of each area were marked and photo documented. The injections were performed by an examiner who was unaware of which liquid had been injected. Compression therapy was performed for one week after the treatment. One and four weeks later the results were controlled by the physician who performed the injections and documented by an independent photographer. The glossy prints of the areas before and four weeks after the treatment were sent to two blinded independent external reviewers. The reviewers noted their evaluation on a visual analogue scale (VAS). The reviewers received each anonymous photodocument twice within 3 weeks. Results: The VAS of both experts showed a significant difference between the results in group 1 and group 2 (p < 0.0001). Median of efficacy was 58.5% in group 1 (verum) and 0.5% in group 2 (placebo). Both experts had a stable intraindividual reliability of 85% and further both raters didn´t differ concerning their ratings. In group 1 (verum) the Pearson correlation coefficient showed a significant correlation between the therapeutic outcome and the age of the treated patients. Conclusions: Injection sclerotherapy of intradermal varicose veins using 0.25 %Polidocanol (Aethoxysklerol) is an efficient treatment that leads to a good aesthetic outcome. In elderly patients sclerotherapy is more efficient.